O-band mode-locked femtosecond praseodymium-doped fluoride fiber laser using a nickel metal-organic framework - Ahmad, Harith; Nizamani, Bilal; Samion, Muhamad Zharif; Mutlu, Saliha; Yılmaz, Sevil Savaşkan; Arsu, Nergis; Thambiratnam, Kavintheran; Ortaç, Bülend (Institute of Electrical and Electronics Engineers Inc., 2025)
Mode-locked fiber lasers are particularly noteworthy due to their compactness, affordability, and reduced losses, making them an attractive option for a variety of uses. Metal-organic frameworks (MOFs) have recently been identified as suitable saturable absorbers (SAs) in lasers operating at 1.5- and 2 μm wavelengths 1, 2. MOFs represent a novel class of porous solid materials formed by the combination of inorganic metal ions and organic linkers. These frameworks exhibit exceptional material properties, such as a large surface area, structural diversity, tunable bandgap, and luminescence, making them highly advantageous for various applications in laser technology. This work presents an ultrafast mode-locked fiber laser operating in the relatively less explored O-band region, utilizing a nickel MOF (Ni-MOF) as a saturable absorber. © 2025 IEEE.